Absorption spectroscopy for the quantitative prediction of lanthanide concentrations in the 3LiCl–2CsCl eutectic at 723 K. Issue 43 (13th September 2016) - Schroll, Cynthia A.; Lines, Amanda M.; Heineman, William R.; Bryan, Samuel A.
Abstract : The absorption spectra of single-component mixtures of six lanthanide chloride salts were obtained in the molten salt eutectic 3LiCl–2CsCl at 723 K, and used to build multivariate regression models to predict concentrations of multi-component mixtures of these metals in solution. Abstract : The absorption spectra of single-component mixtures of erbium(iii ) chloride, holmium(iii ) chloride, neodymium(iii ) chloride, praseodymium(iii ) chloride, samarium(iii ) chloride and thulium(iii ) chloride were obtained in the molten salt eutectic 3LiCl–2CsCl at 723 K and were collected at various concentrations from 0 mM to approximately 200 mM (above which the solutions became saturated). Using these data and Beer's law, the molar absorptivities of the absorption bands for each lanthanide(iii ) chloride were obtained. More sophisticated analysis of the data was completed by building multivariate regression models based on spectra of single-component samples for each lanthanide metal studied. These models were then applied to the measurement/prediction of lanthanide(iii ) concentrations in a validation set comprised of complex multi-component mixtures within the molten-salt solution. The models performed well despite the complexity of the solutions/spectra. Overall, this work presents the UV-vis Beer's law characterization of several lanthanides as well as successful application of multivariate analysis to the measurement/prediction of lanthanide concentrations in molten salts. This represents a significant improvement for materials analysis techniques, applicable for nuclear fuel pyroprocessing methods.